2020
DOI: 10.1192/j.eurpsy.2020.93
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the experience of initiating community-based group physical activity by people with serious mental illness: A systematic review using a meta-ethnographic approach

Abstract: Background: People living with serious mental illness (SMI) experience debilitating symptoms that worsen their physical health and quality of life. Regular physical activity (PA) may bring symptomatic improvements and enhance wellbeing. When undertaken in community-based group settings, PA may yield additional benefits such as reduced isolation. Initiating PA can be difficult for people with SMI, so PA engagement is commonly low. Designing acceptable and effective PA programs requires a better understanding of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 20 publications
(26 citation statements)
references
References 51 publications
1
21
0
Order By: Relevance
“…It could be hypothesized that the Mo-Vo content is suitable for people with major depression, however there may need to be initial counseling sessions devoted to trust and relationship building before the behavior change content is addressed. This hypothesis is supported by qualitative ndings, iterating the importance of the source of physical activity support in people with severe mental illness (42).…”
Section: It Is Known That Participants With Major Depression May Drop...mentioning
confidence: 81%
“…It could be hypothesized that the Mo-Vo content is suitable for people with major depression, however there may need to be initial counseling sessions devoted to trust and relationship building before the behavior change content is addressed. This hypothesis is supported by qualitative ndings, iterating the importance of the source of physical activity support in people with severe mental illness (42).…”
Section: It Is Known That Participants With Major Depression May Drop...mentioning
confidence: 81%
“…This is highly concerning and indicates a need for interventions to facilitate motivation to increase physical activity in this group, as it is highly unlikely that those who do not express a desire to increase physical activity are going to make a change from being inactive to becoming active. 18 Current knowledge regarding effective strategies to motivate those not currently motivated to change health-risk behaviours is limited and requires further investigation. However, it has been suggested that targeting self-efficacy, outcome expectancies, effort and value beliefs, and using motivational interviewing techniques may prove beneficial 19 when facilitating motivation to change.…”
Section: Discussionmentioning
confidence: 99%
“…While there is an abundance of evidence on the bene ts of PA on mood and wellness in the general population, and the physical health bene ts of all people, there is a paucity of research on the e cacy of PA in reducing psychiatric symptom severity in individuals with severe mental illness. This is unique population that faces signi cant barriers to participation in regular PA yet could bene t immensely (9,27). The physical health bene ts of regular PA among this population are well established and were therefore not a focus of this review.…”
Section: Discussionmentioning
confidence: 99%
“…One reason for this difference in PA levels may be the considerable barriers that individuals with SMI face to participating in regular PA. A recent systematic review compiled 16 qualitative studies examining the experiences of individuals with SMI in PA initiation and the unique barriers faced and supports needed, which offers some insight into the lower level of PA in this population. This study identi ed support from a trusted source as a key piece to helping this population overcome some of the unique challenges they face when attempting to engage in regular PA (9).…”
Section: Introductionmentioning
confidence: 99%